(untitled) (Journal of the College of Basic Education, 2022)
Totally twenty six different isolates of Pseudomonas aeuruginosa ( P. aeruginosa ) were collected ,sixteen clinical isolates ( 62% of total group ) were isolated from different samples ( Urine , blood , sputum , wound , ear , eye and throat swabs ) from Medical city hospital in Baghdad, and ten environmental isolates ( 38%of total group ) were isolates from different places of soil and water in the same city . All isolates were diagnosed by bacteriological and biochemical tests . The crud DNA was extracted from all clinical and environmental isolates . BOX-PCR was achieved using BOX1AR primer . The BOX-PCR products were analyzed by horizontal agarose gel electrophoresis . The dendrogram for all isolates was draw by using band-based Jaccard and Dice coefficients where the fingerprints were generated by banding patterns using un weighted pair-group method with arithmetic average ( UPGMA ) , in order to study the relatedness among the clinical and environmental isolates . The results were showed that the crude DNA was suitable to BOX-PCR , and presence of the high similarity in banding patterns of clinical and environmental isolates itselves , which was about 45%-99% and 61%-100% in Jaccard and Dice coefficients respectively . The similarity between these two groups was about 40% and 55% in Jaccard and Dice coefficients respectively . Although , the marked relatedness among all clinical and environmental isolates , this study was concluded presence of genetic variation between the clinical and environmental isolates of this opportunistic bacterium , by using BOX-PCR technique and BOX1AR primer .